The utilization of Ilex paraguariensis aqueous extract as a ergogenic resource in the aerobic exercise - de Lima, Pedro Henrique Barreto (2012)
The study aims to verify whether the consumption of aqueous extract of Ilex paraguariensis influences on performance in aerobic exercise. Through an experimental protocol, the subjects were divided into two groups, one experimental group (EG) consumed the aqueous extract of Ilex paraguariensis and the other control group (CG) consumed pure water. The two groups performed three tests of continuous run of 3200 meters, the first and second without the consumption of the extract and the third with the administration of the extract for the experimental group and the control group for water and their results were compared. There was a mean reduction of 9.6 seconds for the first test and 9.3 seconds relative to the second, with degrees of considerable significance (p ˂ 0.01) in both cases, the group that used the extract aqueous (GE). In the control group (CG), there was an average increase of 2.8 seconds for the first test (p = 0.3) and a mean reduction of 0.1 seconds with the second test (p = 0, 9). We verifieda reduction in execution time in test run 3200 meters in the group that consumed the aqueous extract of Ilex paraguariensis (GE). Despite being statistically significant (p 0.01), the decreases observed were mild, with an average of 9 seconds compared to the test without ingestion of the extract.